Emission factors and detailed chemical composition of smoke particles from the 2010 wildfire season - Vicente, Ana (2018)
This paper complements the information previously published (Atmospheric Environment 45, 641-649) on gaseous and particulate emissions from wildfires in Portugal for summer 2009, in an attempt at obtaining more extensive, complete and representative databases on emission factors and detailed chemical characterisation of smoke particles. Here, emission factors for carbon oxides (CO2and CO), total hydrocarbons (THC), fine (PM2.5) and coarse (PM2.5-10) particles obtained for fires occurring in Portugal in summer 2010 are presented. The carbonaceous content (OC and EC), water-soluble ions, elements and organic composition of smoke particles were, respectively, analysed by a thermal-optical transmission technique, ion chromatography, instrumental neutron activation analysis (INAA) and gas chromatography-mass spectrometry (GC-MS). The particle mass concentrations were in the ranges 0.69-25 mg m-3for PM2.5and 0.048-3.1 mg m-3for PM2.5-10. PM2.5particles represented 91 ± 5.7% of the PM10mass. The OC/EC ratios in fine and coarse particles ranged from 2.5 to 205 and from 1.7 to 328, respectively. The water-soluble ions represented, on average, 3.9% and 2.8% of PM2.5and PM2.5-10mass, respectively. In general, the dominant ions in the water extracts were Na+, NH4+, Cl-and NO3- for the PM2.5fraction, and K+, Mg2+, Ca2+and SO42- for the PM2.5-10fraction. The K+/EC and K+/OC ratios obtained in this study were, on average, 0.22 ± 0.23 and 0.011 ± 0.014 for PM2.5and 0.83 ± 1.0 and 0.024 ± 0.023 for PM2.5-10particles, respectively. The K+/levoglucosan ratio was, on average, 2.0 for PM2.5and 3.1 for PM2.5-10particles. Levoglucosan was detected at mass fractions of 1.6-8.7 mg g-1OC in PM2.5and 2.7-56 mg g-1OC in PM2.5-10. The dominant elements detected in the smoke samples were Na, Br, Cr, Fe, K, Rb and Zn. The most representative organic constituents in the smoke samples were acids, alcohols, terpenoid-type compounds, sugars and phenols, in both size fractions.